Global Public Interests and Dynamic Trends in Osteoporosis From 2004 to 2019: Infodemiology Study - Peng Wang; Qing Xu; Rong-Rong Cao; Fei-Yan Deng; Shu-Feng Lei (JMIR Publications, 2021)
BackgroundWith the prolonging of human life expectancy and subsequent population aging, osteoporosis (OP) has become an important public health issue. ObjectiveThis study aimed to understand the global public search interests and dynamic trends in "osteoporosis" using the data derived from Google Trends. MethodsAn online search was performed using the term "osteoporosis" in Google Trends from January 1, 2004, to December 31, 2019, under the category "Health." Cosinor analysis was used to test the seasonality of relative search volume (RSV) for "osteoporosis." An analysis was conducted to investigate the public search topic rising in RSV for "osteoporosis." ResultsThere was a descending trend of global RSV for "osteoporosis" from January 2004 to December 2014, and a slowly increasing trend from January 2015 to December 2019. Cosinor analysis showed significant seasonal variations in global RSV for "osteoporosis" (P=.01), with a peak in March and a trough in September. In addition, similar decreasing trends of RSV for "osteoporosis" were found in Australia, New Zealand, Ireland, and Canada from January 2004 to December 2019. Cosinor test revealed significant seasonal variations in RSV for "osteoporosis" in Australia, New Zealand, Canada, Ireland, UK, and USA (all P<.001). Furthermore, public search rising topics related to "osteoporosis" included denosumab, fracture risk assessment tool, bone density, osteopenia, osteoarthritis, and risk factor. ConclusionsOur study provided evidence about the public search interest and dynamic trends in OP using web-based data, which would be helpful for public health and policy making.